Pelindungan Bagi Pekerja Migran Indonesia dari Eksploitasi, Perbudakan, dan Diskriminasi - Maftuhatul Adna Mirawan (Fakultas Hukum Universitas Islam Indonesia, 2025)
Migrant workers are one of the largest contributors to foreign exchange earnings for the country, but at the same time, this group is also vulnerable to human rights violations, such as exploitation, modern slavery, and systematic discrimination in the destination country. Migrant workers often face various forms of legal violations, including unfit working conditions, sexual and psychological harassment, unfair wage payments, working under intimidation, and violence. Although Indonesia has ratified various international conventions and has laws regulating the protection of migrant workers, their implementation still faces many challenges. The research method used in this study is the normative legal method. This method involves examining primary legal materials, such as Law No. 18 of 2017 on PPMI, as well as secondary legal materials in the form of literature, scientific journals, and official reports related to migrant workers. Several strategic steps that can support the protection of migrant workers include Acceleration and Improvement of Derivative Regulations, Strengthening Supervision and Law Enforcement, Enhancing the Role of Local Governments and Integrated One-Stop Services, Utilizing Information Technology for Transparency and Accessibility, Enhancing International Cooperation, Empowering and Educating Prospective Migrant Workers, and Actively Involving Civil Society and Migrant Worker Organizations.